Laboratory Management in Improving the Quality of Science Learning - Adi Maladona; Iim Wasliman; Ikka Kartika; R. Supyan Sauri (Journal of Islamicate Studies, 2021)
This study aims to identify and analyze laboratory management in improving the quality of science learning by describing and analyzing planning, organizing, implementing and monitoring as well as innovative ideas. This study uses a qualitative descriptive method with interview data collection techniques, observations and documentation studies and is studied using triangulation. Based on the results of the study, it can be concluded that (1) Planning is carried out by procuring facilities and infrastructure, as well as preparing laboratory administration. (2) The organization does not have a special laboratory and technician (3) Actuating of the science laboratory follows the schedule that has been prepared. However, there are still science teachers who have difficulty in practicum. (4) Controlling through formal and non-formal supervision, monitoring and evaluation. (5) Innovative ideas are carried out by the school in terms of facilities and science teachers in terms of learning. This research produces a research product "Virtual Laboratory Management" which aims to overcome obstacles in science laboratory management during the covid-19 pandemic.